Transformasi Nilai Tambah Cabai Merah di Desa Pondok Meja Melalui Inovasi Teknologi Puree - Ramadani, Suci Putri; Renate, Dharia; Wijaya, Ali Satria; Yusfi, Liza Aulia; Pratami, Tesy (Jurnal Pengembangan dan Pengabdian Masyarakat, 2026)
Red chili is a horticultural commodity with high economic value, but its perishable nature limits its shelf life and increases the risk of postharvest losses. This problem is particularly evident during peak harvest seasons, when oversupply causes market prices to decline. One practical solution is to process red chili into semi-processed products such as puree, which can extend shelf life while adding economic value. This community service program aimed to enhance community knowledge and skills in processing red chili into puree. The program was conducted in Pondok Meja Village, Mestong District, Muaro Jambi Regency, and involved 35 participants, including village officials, farmer groups, PKK members, and local residents. The activities included socialization, counseling, demonstrations, hands-on training, and evaluation using pre-tests and post-tests to measure participants’ improved understanding. The processing of red chili puree involved several stages, including raw material selection, sorting and washing, blanching, grinding using a blender, and hygienic product packaging. The evaluation results indicated an improvement in participants’ understanding after the training, as reflected by an average post-test score of 88.2%. The high level of participation and enthusiasm among participants also indicates that the red chili puree processing technology was well received and has the potential to be implemented by the community to increase the added value of red chili commodities and create opportunities for village-based processed product businesses.